Argon Plasma Coagulation in Bronchoscopy: A Safe and Effective Treatment for Airway Obstruction - Anggi Rizki Utami Nasution; Indra Yovi; Sri Indah Indriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Airway obstruction can significantly impair a patient's quality of life and even become life-threatening. Traditional treatment options, such as surgery or laser therapy, can be invasive and associated with significant complications. Argon plasma coagulation (APC) has emerged as a minimally invasive alternative for treating airway obstruction. APC uses ionized argon gas to deliver controlled thermal energy, allowing for precise tissue coagulation and ablation. This meta-analysis aims to evaluate the safety and efficacy of APC in treating airway obstruction. Methods: A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science databases. Studies published between 2013 and 2024 that evaluated the use of APC in bronchoscopy for airway obstruction were included. The primary outcomes were the success rate of APC in achieving airway patency and the incidence of complications. Results: Seven studies (n=342 patients) met the inclusion criteria. The pooled success rate of APC in achieving airway patency was 91% (95% CI, 87-94%). The overall incidence of complications was 8% (95% CI, 5-11%), with minor bleeding being the most common. Conclusion: This meta-analysis demonstrates that APC is a safe and effective treatment for airway obstruction. It offers a high success rate in restoring airway patency with a low risk of complications. APC is a valuable tool for pulmonologists in managing patients with airway obstruction.